Estudo do comportamento de oviposição em saltos por fêmeas de Aedes aegypti (Diptera: Culicidae) em diferentes densidades de criadouros e a influência da armadilha MosquiTRAP® na redução de ovos e criadouros positivos - Filipe Vieira Santos de Abreu (2010)
Aedes aegypti is the main vector of the dengue virus in Brazil. The oviposition behavior of this vector is important in the control and epidemiology of the disease, since the A. aegypti females perform skip oviposition which result in her dispersion and of the virus. The MosquiTRAP has been used to monitor pregnant females of A. aegypti in urban areas, but its potential for the vector control is questionable. The aim of this work was to study in detail the behavior of skip oviposition of individualized A. aegypti females when exposed to different densities of breeding sites and to evaluate the influence of the MosquiTRAP in reducing deposited eggs and positivity of breeding sites. The study was performed at 24-29C and 60-90% RH in: (1) laboratory conditions, inacrylic boxes (150x50x41cm); (2) semi-field conditions, in fabric cages (2,5 x 2,5 x 2m), in the absence and presence of the MosquiTRAP. For each test, a pregnant female of A. aegypti was released in different densities of breeding sites (1, 2, 4, 8 or 16) where she remained for 96 h. 12 or 15 repetitions were performed for each density of breeding sities. The mean of deposited eggs for female/repetition/treatment ranged from 63,7 ± 13,7 to 81,5 ± 31,5 in laboratory and semi-field conditions, respectively. It was observed that 92,5% of the tested females distributed their eggs in more than one breeding site, when available, characterizing the skip oviposition and that in each test one of the breedingsites received more than 50% of the deposited eggs. The presence of theMosquiTRAP trap in semi-field conditions significantly reduced the total mean of deposited eggs from 72,2 ± 20,5 to 31,9 ± 40,9 and the total mean of breeding sites made positive by the females from 1,8±0,3 to 0,73±0,79; from 2,8± 1,0 to 1,07±1,16; from 3,2±1,5 to 2,07±1,75; and from 5,4±2,6 to 2,33±1,67; at the densities 2, 4, 8 and 16 of breeding grounds, respectively. It was verified that the greater number of A. aegypti captured in the trap occurred during the first 10 hours of experiment. The results suggest that the MosquiTRAP trap is a tool that capture pregnant females of A. aegypti even when competes with different densities of breeding sites and that it is capable to reduce the number of deposited eggs and the positivity of breeding grounds, in the tested conditions.However, future studies in field must be performed to prove its efficiency as a tool in the control of the dengue vector